Coarse and short rice grain-shaped mesoporous hydroxyapatite powder as well as preparation and application thereof
A controlled preparation method using quaternary ammonium salt templates and hydrothermal reactions produces hydroxyapatite powder with uniform shape and size, addressing irregularity issues and meeting safety standards for broader cosmetic applications.
Patent Information
- Application Number
- CN202411183799.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-27
- Publication Date
- 2025-01-03
AI Technical Summary
Current methods for preparing mesoporous hydroxyapatite fail to achieve precise control over morphology and size, resulting in irregular shapes and uneven pore sizes, limiting its applications, particularly in cosmetics where safety regulations restrict the use of nano-sized particles with aspect ratios greater than 3.
A method involving the use of quaternary ammonium salt cationic surfactants as templates, combined with controlled hydrothermal reactions and high-temperature calcination, to produce coarse and short rice-grain-shaped mesoporous hydroxyapatite with adjustable pore sizes and aspect ratios less than 3, using calcium and phosphorus sources and organic or inorganic amines as catalysts.
The method enables the production of hydroxyapatite powder with uniform particle sizes and controlled aspect ratios, suitable for large-scale production, meeting safety standards and enhancing its applicability in cosmetics.
Smart Images

Figure CN119240630A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of advanced porous materials and relates to a coarse and short rice-grain-shaped mesoporous hydroxyapatite powder and a preparation method and application thereof. Background Art
[0002] Hydroxyapatite (HAp), a good biomaterial, has a chemical formula of Ca 10 (PO 4 ) 6 (OH) 2 HAp has been considered as the main mineral component of human bones since the early 19th century, showing its deep background in the field of biomaterials. Over time, people have conducted in-depth research on the characteristics and applications of HAp, laying the foundation for its wide application in many fields.
[0003] HAp's excellent biocompatibility makes it an ideal material for bone-related applications. In the 1970s, researchers found that HAp implanted in vivo can integrate well with surrounding bone tissue, a discovery that further promoted the application of HAp in the biomedical field, especially in orthopedics and dentistry.
[0004] In addition, as an important mesoporous material, inorganic mesoporous hydroxyapatite has been widely used in adsorption, catalysis, filtration, energy storage and beauty due to its high porosity, large specific surface area, stable chemical properties, low cost and non-toxicity. Especially in the field of cosmetics, hydroxyapatite plays an important role in maintaining dental and oral health due to its unique properties such as non-toxicity, high strength, corrosion resistance, oil control and absorption, and good affinity with teeth.
[0005] Hydroxyapatite has attracted much attention for its teeth whitening effect. It can effectively inhibit the growth of dental plaque and promote the remineralization of tooth enamel, thereby improving the appearance of teeth. In addition, it can also soothe dentin sensitivity and provide users with a more comfortable oral experience.
[0006] However, although the preparation of mesoporous hydroxyapatite has become quite popular, its irregular morphology and uneven pore size still limit its application. The ideal mesoporous hydroxyapatite should have a narrow pore size distribution, good thermal and hydrothermal stability, and a regular shape. Such a material has a larger specific surface area, higher surface adsorption and ion exchange properties, and can more effectively repair teeth and skin.
[0007] It is worth noting that despite the many advantages of hydroxyapatite, its use is also subject to certain restrictions in some cases. For example, in the latest EU cosmetics regulations, the use of hydroxyapatite (nano) is restricted, which is mainly based on the safety and environmental impact of nanomaterials. Therefore, in the process of promoting the application of hydroxyapatite, its safety and effectiveness need to be fully considered. The European Union Consumer Safety Scientific Committee SCCS believes that the maximum safe concentration of hydroxyapatite (nano) in toothpaste is 10%, and the maximum safe concentration in mouthwash is 0.465%. This safety assessment only applies to hydroxyapatite (nano) with the following characteristics: composed of rod-shaped particles, of which at least 95.8% (number of particles) have an aspect ratio of less than 3, and the remaining 4.2% have an aspect ratio of no more than 4.
[0008] At present, most of the reported mesoporous hydroxyapatite materials are irregular micron particles with poor particle uniformity and uncontrollable particle size. Due to insufficient understanding of the self-assembly process, the current preparation methods cannot achieve precise control of its morphology and size. Therefore, it is still an important research direction to develop a simple and controllable preparation method to prepare mesoporous hydroxyapatite particles with mesoporous channels, adjustable morphology and size, and an aspect ratio of less than 3, forming a rough and short rice grain shape. Summary of the invention
[0009] The purpose of the present invention is to provide a coarse and short rice-grain-shaped mesoporous hydroxyapatite powder and its preparation and application, so as to prepare a coarse and short rice-grain-shaped mesoporous hydroxyapatite powder with high specific surface area, large pore volume, uniform and size-adjustable pore size.
[0010] The purpose of the present invention can be achieved by the following technical solutions:
[0011] In a first aspect, the present invention provides a method for preparing a coarse and short rice-grain-shaped mesoporous hydroxyapatite powder, comprising the following steps:
[0012] (1) dissolving the template in a solvent and adding a phosphorus source to obtain a first solution;
[0013] (2) weighing a calcium source and dissolving it in another solvent to obtain a second solution;
[0014] (3) pouring the second solution into the first solution, adding an inorganic or organic amine as a catalyst, and reacting once to obtain a suspension;
[0015] (4) The obtained suspension is transferred into a hydrothermal reaction vessel to carry out a hydrothermal secondary reaction, and the obtained product is calcined at high temperature to remove the template agent, thereby obtaining a coarse and short rice-grain-shaped mesoporous hydroxyapatite material.
[0016] Furthermore, in step (1), the template is selected from one or more quaternary ammonium salt cationic surfactants.
[0017] Furthermore, in step (1), the template agent is hexadecyltrimethylammonium bromide.
[0018] Furthermore, in step (1), the phosphorus source is one or a combination of potassium dihydrogen phosphate, potassium phosphate, ammonium dihydrogen phosphate or diammonium hydrogen phosphate.
[0019] Furthermore, in step (2), the calcium source is one or more of calcium chloride, calcium nitrate or calcium phosphate.
[0020] Furthermore, the catalyst is one or more of ammonia, amide, aromatic amine or alicyclic amine.
[0021] Furthermore, the mass ratio of the template, phosphorus source and calcium source is (0.2-2.5): (0.2-1.0): (1-1.5).
[0022] Furthermore, the amount of the catalyst added satisfies: adjusting the pH value of the current solution system to 8 to 9.5. Specifically, the catalyst can also be added when preparing the first solution, and the amount of the catalyst added also satisfies the pH value of the solution to 8 to 9.5.
[0023] Furthermore, in step (3), the temperature of the primary reaction is room temperature to 70° C., and the reaction time is 2.5 to 36 hours.
[0024] Furthermore, in step (4), the temperature of the hydrothermal secondary reaction is 80-160° C., the time is 12-36 hours, and the reaction pressure is 1-3 MPa.
[0025] Furthermore, high temperature calcination is carried out in an air atmosphere, with a holding temperature of 600 to 1000° C. and a time of 3 to 12 hours.
[0026] Furthermore, the solvents used in step (1) and step (2) are independently selected from one or more of water, ethanol, and butanediol.
[0027] On the other hand, the present invention also provides a coarse and short rice-grain-shaped mesoporous hydroxyapatite powder, which is prepared by any of the above-mentioned preparation methods, wherein the particle size of the mesoporous hydroxyapatite powder is 1 to 20 μm (Bettersize 2000 laser particle size distribution instrument test), the rice grain size is 30-100 nm (SEM test), and the specific surface area is 50 to 150 m 2 / g, pore diameter is 3-5.5nm, pore volume is 0.1-0.4cm 3 / g.
[0028] In a third aspect, the present invention also provides a use of coarse and short rice-grain-shaped mesoporous hydroxyapatite powder in daily chemical products or cosmetics.
[0029] Compared with the prior art, the present invention has the following advantages:
[0030] (1) The solution of the present invention can accurately control the aspect ratio of the final mesoporous hydroxyapatite powder to be less than 3, and the industrial yield is higher.
[0031] (2) The method is simple, wet preparation, and the raw materials are readily available, which is suitable for large-scale production and has broad application prospects in the cosmetics field. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 Scanning electron microscope (SEM) photos of mesoporous hydroxyapatite powder synthesized in Example 1 (left) and Example 4 (right).
[0033] Figure 2 This is a table of longitudinal and transverse dimension data and a scanning electron microscope image of the mesoporous hydroxyapatite powder synthesized in Example 1.
[0034] Figure 3 The transmission electron microscope (TEM) photograph and the vertical and horizontal dimension data list of the mesoporous hydroxyapatite synthesized in Example 4 are shown.
[0035] Figure 4 The electron microscope photograph and the vertical and horizontal dimension data list of the mesoporous hydroxyapatite synthesized in Comparative Example 1 are shown.
[0036] Figure 5 The electron microscope photograph and the vertical and horizontal dimension data list of the mesoporous hydroxyapatite synthesized in Comparative Example 2 are shown.
[0037] Figure 6 The electron microscope photograph and the vertical and horizontal dimension data list of the mesoporous hydroxyapatite synthesized in comparative example 3 are shown. DETAILED DESCRIPTION
[0038] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and specific operation process, but the protection scope of the present invention is not limited to the following embodiments.
[0039] In the following examples, unless otherwise specified, raw materials or processing techniques are conventional commercially available raw materials or conventional processing techniques in the art.
[0040] Embodiment 1:
[0041] (1) At 70°C, dissolve 2.5 g of CTAB (cetyltrimethylammonium bromide) in 50 mL of deionized water, then add 1.0 g of KH 2 PO 4 , defined as solution 1). At the same time, NH 3 ·H 2O was adjusted to pH = 9.0.
[0042] (2) 1.5 g CaCl 2 Dissolve in 50 mL of deionized water (designated as solution 2).
[0043] (3) Stir vigorously with magnetic stirring, pour solution 2 into solution 1, add NH 3 ·H 2 O, adjust pH = 9.0.
[0044] (4) React at 70°C for 2.5 hours.
[0045] (5) The prepared suspension was transferred into a polytetrafluoroethylene autoclave (hydrothermal autoclave) and crystallized at 160°C for 24 hours with the pressure controlled at 2 MPa.
[0046] Embodiment 2:
[0047] (1) At 50°C, 3 g of CTAB was dissolved in 50 mL of deionized water, and then 2.1 g of KH 2 PO4, defined as solution 1. Add NH 3 ·H 2 O was adjusted to pH=9.
[0048] (2) 3 g CaCl 2 Dissolve in 50 mL of deionized water (designated as solution 2).
[0049] (3) With vigorous magnetic stirring, add solution 2 dropwise to solution 1 and add NH 3 ·H 2 O, pH = 9.0.
[0050] (4) React at 70°C for 8 hours.
[0051] (5) The prepared suspension was transferred into a polytetrafluoroethylene autoclave (hydrothermal autoclave) and crystallized at 100°C for 24 hours with the pressure controlled at 2 MPa.
[0052] Embodiment 3:
[0053] (1) At room temperature, dissolve 2.5 g of CTAB in 50 mL of deionized water, then add 1.0 g of KH 2 PO 4 , which is called solution 1. Add NH 3 ·H 2 O was adjusted to pH=8.
[0054] (2) 1.5 g Ca(NO 3 ) 2 Dissolve in 50 mL of deionized water and name it Solution 2.
[0055] (3) Stir vigorously with magnetic stirring, pour solution 2 into solution 1, add NH 3 ·H 2 O, pH = 9.0.
[0056] (4) React at room temperature for 12 hours.
[0057] (5) The prepared suspension was transferred into a polytetrafluoroethylene autoclave (hydrothermal autoclave) and crystallized at 80°C for 48 hours with the pressure controlled at 2 MPa.
[0058] Embodiment 4:
[0059] (1) At room temperature, 3 g of CTAC (hexadecyltrimethylammonium chloride) was dissolved in 50 mL of deionized water, and then 2.1 g of KH 2 PO 4 , (designated as solution 1). Add NH 3 ·H 2 O was adjusted to pH = 9.0.
[0060] (2) Dissolve 3 g of Ca3(PO4)2 in 50 mL of deionized water (designated as solution 2).
[0061] (3) With vigorous magnetic stirring, add solution 2 dropwise to solution 1 and add NH 3 ·H 2 O, pH = 9.0.
[0062] (4) React at room temperature for 36 hours.
[0063] (5) The prepared suspension was transferred into a polytetrafluoroethylene autoclave (hydrothermal autoclave) and crystallized at 120°C for 24 hours with the pressure controlled at 2 MPa.
[0064] Figure 1 The electron microscope photos of the mesoporous hydroxyapatite powder synthesized in Example 1 and Example 4 are shown respectively. It can be seen from the figure that the particle shape and aspect ratio of the product of the present invention are adjustable, and most of them are less than 3. In addition, Figure 2 and 3 A list of longitudinal and transverse dimension data of the mesoporous hydroxyapatite powder synthesized in Example 1 and Example 4 is also given, wherein the odd-numbered numbers are the longitudinal dimension data, and the even-numbered numbers are the corresponding transverse dimension data. The specific correspondence is that number 1 (longitudinal) corresponds to number 2 (transverse), and number 3 (longitudinal) corresponds to number 4 (transverse).
[0065] Comparative Example 1:
[0066] (1) At 70°C, dissolve 2.5 g of CTAB (cetyltrimethylammonium bromide) in 50 mL of deionized water, then add 1.0 g of K2 HPO 4 , defined as solution 1). At the same time, NH 3 ·H 2 O was adjusted to pH = 9.0.
[0067] (2) 1.5 g CaCl 2 Dissolve in 50 mL of deionized water (designated as solution 2).
[0068] (3) Stir vigorously with magnetic stirring, pour solution 2 into solution 1, add NH 3 ·H 2 O, adjust pH = 9.0.
[0069] (4) React at 70°C for 2.5 hours.
[0070] (5) The prepared suspension was transferred into a polytetrafluoroethylene autoclave (hydrothermal autoclave) and crystallized at 160°C for 24 hours.
[0071] Figure 3 The electron microscope photograph of the mesoporous hydroxyapatite powder synthesized in Comparative Example 1 shows that the longitudinal size data of the particles correspond to Figure 3 The particle sizes corresponding to the numbers 1, 3, 5, 7, 9, 11, and 13 in the table data, and the lateral size data correspond to the particle sizes corresponding to the numbers 2, 4, 6, 8, 10, 12, and 14 in the table data, respectively. The proportion of particles with an aspect ratio greater than 3 has increased significantly.
[0072] The reason for the analysis is that the K used in Comparative Example 1 and Example 1 2 HPO 4 and KH 2 PO 4 The phosphorus sources in the present invention have significantly different properties. For example, dipotassium hydrogen phosphate is an acidic salt because it can produce acidic hydrogen ions in aqueous solution, which reduces the pH value; while potassium dihydrogen phosphate is an alkaline salt because it can produce alkaline hydroxide ions in aqueous solution, which increases the pH value. In addition, the KH 2 PO 4 Due to its acidity, the number of hydrogen bond donors provided is 2, relative to K 2 HPO 4 The number of hydrogen bond donors provided is 1 more, which can further affect the micelle shape of the template agent, thereby better controlling the aspect ratio range of the synthesized mesoporous hydroxyapatite.
[0073] Comparative Example 2:
[0074] Compared with Example 1, most of the steps are the same, except that the hydrothermal treatment in the autoclave is performed under normal pressure instead.
[0075] (1) At 70°C, dissolve 2.5 g of CTAB (cetyltrimethylammonium bromide) in 50 mL of deionized water, then add 1.0 g of KH 2 PO 4 , defined as solution 1). At the same time, NH 3 ·H 2 O was adjusted to pH = 9.0.
[0076] (2) 1.5 g CaCl 2 Dissolve in 50 mL of deionized water (designated as solution 2).
[0077] (3) Stir vigorously with magnetic stirring, pour solution 2 into solution 1, add NH 3 ·H 2 O, adjust pH = 9.0.
[0078] (4) React at 70°C for 2.5 hours.
[0079] (5) and reacted at 160°C and normal pressure for 24 hours.
[0080] Figure 4 The electron microscope photograph and longitudinal and transverse size data of the mesoporous hydroxyapatite powder synthesized in Comparative Example 2. It can be seen from the figure that the longitudinal size data are the particle sizes corresponding to numbers 1, 3, 5, 7, 9, 11, 13, 15, 17, and 19, respectively, and the corresponding transverse size data of the particles are the particle sizes corresponding to numbers 2, 4, 6, 8, 10, 12, 14, 16, 18, and 20, respectively. The aspect ratios are less than 3 in some cases and greater than 3 in some cases.
[0081] Comparative Example 3:
[0082] (1) At 70°C, dissolve 2.5 g of CTAB (cetyltrimethylammonium bromide) in 50 mL of deionized water, then add 1.0 g of KH 2 PO 4 , defined as solution 1). At the same time, NH 3 ·H 2 O was adjusted to pH=12.
[0083] (2) 1.5 g CaCl 2 Dissolve in 50 mL of deionized water (designated as solution 2).
[0084] (3) Stir vigorously with magnetic stirring, pour solution 2 into solution 1, add NH 3 ·H 2 O, adjust pH = 12.
[0085] (4) React at 70°C for 2.5 hours.
[0086] (5) The prepared suspension was transferred into a polytetrafluoroethylene autoclave (hydrothermal autoclave) and crystallized at 160°C for 24 hours with the pressure controlled at 2 MPa.
[0087] Figure 5 This is an electron microscope photograph of the synthetic mesoporous hydroxyapatite powder synthesized in Comparative Example 3. It can be seen from the figure that the longitudinal dimension data are the particle sizes corresponding to numbers 1, 3, 5, 7, 9, 11, 13, 15, 17, and 19 in the table, and the corresponding lateral dimension data of the particles are the particle sizes corresponding to numbers 2, 4, 6, 8, 10, 12, 14, 16, 18, and 20 in the table. A large portion of the obtained hydroxyapatite powder has an aspect ratio greater than 3 and the particle size is uneven.
[0088] After testing, most of the hydroxyapatite powders obtained in Comparative Example 3 have an aspect ratio greater than 3 and uneven particle sizes. Figure 5 Electron microscope photograph.
[0089] Embodiment 5-7:
[0090] Compared with Example 1, the phosphorus source is adjusted to an equal molar amount of potassium phosphate, ammonium dihydrogen phosphate or diammonium hydrogen phosphate.
[0091] Embodiment 8:
[0092] Compared with Example 1, the mass ratio of the template, the phosphorus source and the calcium source is adjusted to 0.2:0.2:1.5.
[0093] Embodiment 9:
[0094] Compared with Example 1, the mass ratio of the template, the phosphorus source and the calcium source is adjusted to 2.5:1.0:1.
[0095] Embodiment 10:
[0096] Compared with Example 1, the reaction temperature in step (4) is adjusted to 70° C. and the reaction time is 4 h.
[0097] Embodiment 11
[0098] Compared with Example 1, the temperature of the hydrothermal reaction is adjusted to 80-160° C., the time is adjusted to 12-36 h, and the reaction pressure is 1 MPa.
[0099] Embodiment 12:
[0100] Compared with Example 1, the temperature of the hydrothermal reaction is adjusted to 80-160° C., the time is adjusted to 12-36 h, and the reaction pressure is 3 MPa.
[0101] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.
Claims
1. A method for preparing coarse and short rice-grain-shaped mesoporous hydroxyapatite powder, characterized in that: The following steps are involved: (1) dissolving a template in a solvent and adding a phosphorus source to obtain a first solution; (2) weighing a calcium source and dissolving it in another solvent to obtain a second solution; (3) pouring the second solution into the first solution, adding an inorganic or organic amine as a catalyst, and reacting once to obtain a suspension; (4) The obtained suspension is transferred into a hydrothermal reaction vessel to carry out a hydrothermal secondary reaction, and the obtained product is calcined at high temperature to remove the template agent, thereby obtaining a coarse and short rice-grain-shaped mesoporous hydroxyapatite material.
2. The method for preparing a coarse and short rice-grain-shaped mesoporous hydroxyapatite powder according to claim 1, characterized in that: In step (1), the template is selected from one or more quaternary ammonium salt cationic surfactants.
3. The method for preparing the coarse and short rice-grain-shaped mesoporous hydroxyapatite powder according to claim 1, characterized in that: In step (1), the phosphorus source is one or a combination of potassium dihydrogen phosphate, potassium phosphate, ammonium dihydrogen phosphate or diammonium hydrogen phosphate.
4. The method for preparing the coarse and short rice-grain-shaped mesoporous hydroxyapatite powder according to claim 1, characterized in that: In step (2), the calcium source is one or more of calcium chloride, calcium nitrate or calcium phosphate.
5. The method for preparing the coarse and short rice-grain-shaped mesoporous hydroxyapatite powder according to claim 1, characterized in that: The catalyst is one or more of ammonia water, amide, aromatic amine or alicyclic amine.
6. The method for preparing the coarse and short rice-grain-shaped mesoporous hydroxyapatite powder according to claim 1, characterized in that: The mass ratio of the template, phosphorus source and calcium source is (0.2-2.5): (0.2-1.0): (1-1.5); The amount of the catalyst added is such that the pH value of the current solution system is adjusted to 8-9.
5.
7. The method for preparing the coarse and short rice-grain-shaped mesoporous hydroxyapatite powder according to claim 1, characterized in that: The solvents used in step (1) and step (2) are independently selected from one or more of water, ethanol and butanediol.
8. The method for preparing the coarse and short rice-grain-shaped mesoporous hydroxyapatite powder according to claim 1, characterized in that: In step (3), the temperature of the primary reaction is room temperature to 70° C., and the reaction time is at least 1 h; In step (4), the temperature of the hydrothermal secondary reaction is 80-160° C., the time is 12-36 hours, and the reaction pressure is 1-3 MPa; The high temperature calcination is carried out in an air atmosphere, with a holding temperature of 600 to 1000°C and a time of 3 to 12 hours.
9. A coarse and short rice-grain-shaped mesoporous hydroxyapatite powder, prepared by the preparation method according to any one of claims 1 to 8, characterized in that: The particle size of the mesoporous hydroxyapatite powder is 1 to 20 μm, and the specific surface area is 50 to 150 m 2 / g, pore diameter is 3-5.5nm, pore volume is 0.1-0.4cm 3 / g.
10. Use of the coarse and short rice-grain-shaped mesoporous hydroxyapatite powder according to claim 9 in daily chemical products or cosmetics.
